Perspektif Kewirausahaan Sosial dalam Kelompok Usaha Nata de Coco Sejahtera Mandiri di Nagari Balai Baiak III Koto, Kabupaten Padang Pariaman - Helmy Gusriani; Ferdhinal Asful; Zulvera Zulvera (Jurnal Pertanian Khairun, 2023)
This study aims to describe the application of social entrepreneurship elements and describe the canvas business model for social entrepreneurship development in the Nata de Coco Sejahtera Mandiri business group. This research was conducted for 1 month (July-August 2022). This type of research is descriptive qualitative using the case study method. The data used are primary data and secondary data obtained through observation, in-depth interviews and documentation. For the first objective, the data was analyzed using the Miles and Huberman data analysis model and for the second objective it was analyzed descriptively qualitatively, then an assessment of the social benefits of the program was carried out using the Social Return of Investment (SRoI) method. The results of this study indicate that the elements of social entrepreneurship have been implemented by the Nata de Coco Sejahtera Mandiri business group in the form of social values, civil society, innovation and economic activity, but have not optimally provided benefits. Nine elements in the business model canvas for social entrepreneurship development have been implemented consisting of customer segmentation, value proposition and social value, channels, customer relationships, revenue streams and community reinvestment, key activities, key resources, key partners, and cost structure, but not yet optimal. Based on the SRoI assessment of the Nata de Coco Sejahtera Mandiri business group, it can be concluded that the benefits generated are 1:0.03, meaning that social entrepreneurship activities have not been able to create sustainability benefits for stakeholders and have not been able to create social business independence, because the resulting SRoI ratio is less than 1 (1). We recommend that the Nata de Coco Sejahtera Mandiri business group optimize the management of environmental aspects by managing liquid waste from the production of Nata de Coco produced, increasing the participation of local residents and increasing the scale of social business.Keywords : Social Entrepreneurship, Nata de Coco, SRoI